Bacillus subtilis based probiotic improved bone mass and altered brain serotoninergic and dopaminergic systems in broiler chickens. (October 2018) - Yan, F.F.; Wang, W.C.; Cheng, H.W.
Graphical abstract: Highlights: Probiotic increases bone mineral density and content of both tibia and femur. Probiotic increases serotonin in the raphe nuclei. Probiotic reduces norepinephrine and dopamine in the hypothalamus. Probiotic increases dopamine turnover in the hypothalamus. Abstract: The aim of the study was to assess the effects of dietary supplementation of a Bacillus subtilis based probiotic on broiler bone health. After 43 days, probiotic fed broilers had greater bone mineralization, wall thickness, size, and weight of tibias and femurs compared to the controls. We further found that probiotic fed broilers also had higher serum calcium levels at day 14 and a trend of lower serum c-terminal telopeptide of type I collagen levels, a bone resorption indicator, at day 43. Moreover, the level of serotonin was increased in the raphe nuclei, whereas the concentrations of norepinephrine and dopamine were decreased in the hypothalamus of broilers fed probiotic at day 43. These results indicate that dietary supplementation of a Bacillus subtilis based probiotic improves broiler bone traits, most likely through increased calcium intestinal absorption and reduced bone resorption by inhibiting sympathetic activity via the central serotonergic system.